Eficacia de las técnicas de facilitación neuromuscular propioceptiva dentro del tratamiento fisioterapéutico en pacientes que presentan lesiones de miembro inferior atendidos en el departamento de fisioterapia del hospital de brigada nº11 galápagos en el período julio-diciembre del 2009” - Robalino Alvarado, Mónica Alexandra (2011)
This research work with the title of effectiveness of proprioceptive neuromuscular facilitation techniques in lower limb injuries is a matter of great importance since it is an excellent method for rapid and effective improvement in flexibility, functionality, since the purpose is to obtain specific responses of the neuromuscular system after stimulation of the proprioceptors, the objective of this research is to formulate a treatment plan for the respective lesions of patients who require it. Proprioceptive Neuromuscular Facilitation began with Dr. Herman Kabatt, neurophysiologist, in the 40's, emerging as a therapeutic method of muscle rehabilitation in victims of strokes and accidents, then was adopted by the sport and physical activity are currently used to treat many neurological and orthopedic ailments. It evaluates the strengths and weaknesses and deal with patterns of movement and posture, in which the therapist must understand the sequence of development and normal movement components in order to give proper treatment to each patient. These patterns require interaction between the proximal parts (head, neck and trunk) and distal parts (limbs).